Ten years after entry into force of the Stockholm Convention: What do air monitoring data tell about its effectiveness? - Wöhrnschimmel, Henry; Scheringer, Martin; Bogdal, Christian; Hung, Hayley; Salamova, Amina; Venier, Marta; Katsoyiannis, Athanasios; Hites, Ronald A; Hungerbuhler, Konrad; Fiedler, Heidelore (Environmental pollution (Barking, Essex, 2016)
More than a decade ago, the Stockholm Convention on Persistent Organic Pollutants (POPs), one of the multilateral environmental agreements administered by the United Nations Environment Programme (UNEP), entered into force. The objective of this Convention is to protect human health and the environment by controlling the releases of POPs. According to its Article 16, the effectiveness of the Stockholm Convention shall be evaluated using comparable monitoring data on the presence of POPs as well as their regional and global environmental transport. Here, we present a time series analysis on atmospheric POP concentrations from 15 monitoring stations in North America and Europe that provide long-term data and have started operations between 1990 and 2003. We systematically searched for temporal trends and significant structural changes in temporal trends that might result from the provisions of the Stockholm Convention. We find that such structural changes do occur, but they are related mostly to effects of national regulations enforced prior to the implementation of the Stockholm Convention, rather than to the enforcement of the provisions laid out in the Convention. One example is that concentrations of polychlorinated biphenyls, many of which started to decrease rapidly during the 1990s. Also effects of chemical transport and fate, for instance the re-volatilization of POPs from secondary sources, are thought to be a cause of some of the observed structural changes. We conclude that a decade of air monitoring data has not been sufficient for detecting general and statistically significant effects of the Stockholm Convention. Based on these lessons, we present recommendations for the future operation of existing monitoring programs and advocate for a stricter enforcement of the provisions of the Stockholm Convention, in the current absence of proof for its effectiveness.
Keywords: monitorování životního prostředí; látky znečišťující vzduch; Air Pollutants; mezinárodní spolupráce; Air monitoring; Europe; Time Factors; polychlorované bifenyly; Effectiveness evaluation; Severní Amerika; Stockholm Convention; Evropa; Time series analysis; Environmental Monitoring; International Cooperation; North America; znečištění životního prostředí; Environmental Pollution; Polychlorinated Biphenyls; Humans; časové faktory; lidé